Performance Analysis of Electric Locomotive using Matrix Converter - T, Prathab; K, Yasoda (Journal of Electronics and Informatics, 2023)
The conventional type electric locomotive consists of traction transformer, traction converter and three phase induction motor. The conventional type traction converter contains rectifier and inverter which makes it huge, less efficient and difficult to maintain. In this research, the conventional traction converter is replaced by a single matrix converter (AC to AC converter) with bidirectional switches. The proposed converter is analyzed using different Pulse Width Modulation techniques namely sinusoidal pulse width modulation, and space vector pulse width modulation, and the performance of proposed converter is observed by using MATLAB.
Keywords: Matrix Converter; PWM techniques; traction motor; Total Harmonic Distortion